ANALISA PERBANDINGAN BIAYA DAN WAKTU PELAKSANAAN BETON CAST IN SITU DENGAN PRE CAST STUDI KASUS : PENGENDALIAN BANJIR SISTEM LOA JANAN DAN RAPAK DALAM SAMARINDA - SULISTIO, JOKO (KURVA S JURNAL MAHASISWA, 2018)
In the implementation of a construction there are several alternatives in its implementation which are used as cast in situ concrete which in its construction is planned in advance, all concrete work is designed manually by assembling reinforcement in the building made. While concrete pre cast (fabrication) is produced from the production process where the manufacturing location is different from the location where the structural elements will be used. This study aims to compare the cost and execution time of a concrete cast in situ precast with the Flood Control System for Loa Janan and Rapak Dalam Systems using data such as image data, material prices, wages and equipment. And from the results of the calculation analysis, the results of the concretion on the project are obtained that the concrete in situ requires 138 days with a total cost of Rp. 1,277,041,400.00, and the pre cast concrete takes 140 days with a total cost of Rp. 1,285. 503,600.00 So that from this research, the comparison result is that the implementation of cast in situ concrete is considered cheaper and more efficient with a cheaper price ratio of Rp. 8,462,629.65 and 3 days faster time for flood control work for Loa Janan and Rapak Dalam systems.